A modeled perovskite solar cell structure with a Cu2O hole-transporting layer enabling over 20% efficiency by low-cost low-temperature processing. (January 2019) - Lin, Lingyan; Jiang, Linqin; Li, Ping; Fan, Baodian; Qiu, Yu
Abstract: We introduce Cu2 O as a hole-transporting material in perovskite solar cells. Device modeling with a configuration of glass/fluorine-doped tin oxide/ZnO/perovskite/Cu2 O/carbon was performed by SCAPS, a solar cell capacitance simulator. The simulation results indicate that the device performance is greatly dependent on the defect densities and thickness of the perovskite absorber. An absorber thickness of 500 nm was optimum for efficient light absorption. The defect states at the perovskite/ZnO interface had a stronger influence on solar cell performance than those at the Cu2 O/perovskite interface; therefore, to further improve photovoltaic performance, we should pay particular attention to the perovskite/ZnO interface. Proper interface modification and passivation to lower defect densities of the interface below 10 16  cm −3 was essential. The impact of acceptor density and hole mobility of the hole-transport layer on device performance further confirmed that Cu2 O is a suitable hole-transport layer for perovskite solar cells. Finally, to achieve better photovoltaic performance, a back-contact material with a high work function is very necessary. Highlights: A device with the structure of glass/fluorine-doped tin oxide/ZnO/perovskite/Cu2 O/carbon is simulated. The optimal thickness of the absorber is 500 nm. Absorber defect density under 10 14  cm −3, interface defect density under 10 16  cm −3 is needed for good device performance. A back-contact work function larger than 4.9 eV is beneficial.